WOOLWORTHS AUSTRALIA AND WALMART US: BEST PRACTICES IN SUPPLY CHAIN COLLABORATION - Verdi Arli; Sean Dylke; Rosie Burgess; Romain Campus; Evita Soldo (Universitas Hayam Wuruk Perbanas, 2013)
This study analyses retail industries with the efforts of their supply chain collaboration (SCC) frommanufacturers to consumers. It also describes the ways of identifying collaboration partners and buildingpartnership for sharing information, thus representing the best practices in such efforts. The successof building the collaboration in terms of supply chain is described through the observation and analyseson the journey undertaken by both Walmart US, and Woolworths Australia. This is said to have enabledthe retailers to achieve greater organizational performance through driving common objectives in partnershipwith their supply network. For examples there some empirical successes as achieved by Woolworthssuch as saving of approximately AUD75M within the first two years of project commencement,reduction in lead time of getting point-of-sale information from two weeks to every Monday morning forthe previous week, integration of information technology into supply chain management, and improvementin sales by AUD7 billion. It can be generalized that through the sharing of knowledge, resources,information, profits and risks, the companies are able to position themselves in an advantageous spot,where operational efficiencies and financial cost savings are paramount.